The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.2c01918
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis of Acetate by Sporomusa ovata–CdS Biohybrid System

Abstract: Sporomusa ovata, a typical electroautotrophic microorganism, has been utilized in bioelectrosynthesis for carbon dioxide fixation to multicarbon organic chemicals. However, additional photovoltaic devices are normally needed to convert photo energy to electric energy to power the carbon dioxide fixation, which restricts the overall energy conversion efficiency. Herein, we report Sporomusa ovata−CdS biohybrids for artificial photosynthesis driven by light without any other power source. The quantum yield can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Besides M. thermoacetica , other acetogens have also been utilized to construct PBSs. Sporomusa ovata ( S. ovata ) is one of the acetogens as well as electro-active bacteria (EAB) and has been utilized in microbial electrosynthesis systems for CO 2 fixation, driven by electricity directly , or electricity converted from solar energy by photovoltaic devices. , He et al proposed a PBS based on S. ovata by bioprecipitating CdS-NPs onto its surface through an analogical process of M. thermoacetica -CdS construction. The S. ovata -CdS biohybrid reaches a high QY of 16.8 ± 9% and an active duration time of 5 days.…”
Section: Construction and Application Of Whole-cell-based Biohybrid S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides M. thermoacetica , other acetogens have also been utilized to construct PBSs. Sporomusa ovata ( S. ovata ) is one of the acetogens as well as electro-active bacteria (EAB) and has been utilized in microbial electrosynthesis systems for CO 2 fixation, driven by electricity directly , or electricity converted from solar energy by photovoltaic devices. , He et al proposed a PBS based on S. ovata by bioprecipitating CdS-NPs onto its surface through an analogical process of M. thermoacetica -CdS construction. The S. ovata -CdS biohybrid reaches a high QY of 16.8 ± 9% and an active duration time of 5 days.…”
Section: Construction and Application Of Whole-cell-based Biohybrid S...mentioning
confidence: 99%
“…Both of the two metabolic pathways were involved in providing large amounts of reducing equivalents (NADH) and ATP for the WLP. Inspired by the work of M. thermoacetica -CdS biohybrid system, He et al proposed the S.ovata -CdS biohybrid for CO 2 reduction. Proteomic and metabolomic methodologies, were also utilized in the mechanism study of the PBS, which revealed that some key proteins, e.g., Fd, Fp, formate-tetrahydrofolate ligase (Fhs), 5-methyltetrahydrofolate/corrinoid iron–sulfur protein methyltransferase (MeTr), thioredoxin, and rubrerythrin, were expressed at high levels in the presence of CdS and under light irradiation.…”
Section: Charge Transfer Mechanisms In Photosensitized Biohybrid Systemsmentioning
confidence: 99%
“…Microbial synthesis is the use of organic matter and carbon dioxide (CO 2 ) through a wide range of microbial metabolic pathways and a variety of synthase production to produce high-value-added chemicals, such as biofuels, drug precursors, and biological materials. Compared with chemical synthesis, microbial synthesis is a more effective and environmentally friendly method . Based on the biohybrid semiconductor–microbial photosynthetic system, one can convert and store solar energy into chemical energy, such as hydrogen production, , CO 2 reduction, , and N 2 fixation. In the photosynthetic biohybrid system, artificial photosensitizers, i.e., semiconductors are used to harvest light and generate electrons, which can be further transported by electron transport protein to reach the rich metabolic pathways in the bacteria for biosynthesis. Generally, inorganic photosynthetic systems suffer from poor specificity, generating only simple C1 products (CO, methanol, methane, or formic acid).…”
Section: Introductionmentioning
confidence: 99%
“…The natural photosynthesis process is the best strategy for harnessing CO 2 from the air. , As one of the most abundant marine microorganisms, diatoms are responsible for more than 50% of global CO 2 fixation and account for approximately 40% of marine primary productivity . Combining phytoplankton with nanomaterials into biohybrid systems provides the potential to decrease atmospheric CO 2 levels. , However, the cytotoxicity and high cost of engineered nanomaterials limit the development of sustainable photosynthetic biohybrid systems. For example, most biocompatible materials (e.g., carbon or graphite) exert cyto- and genotoxic effects on stem cells, microorganisms, and even animals. , Engineered manganese-based nanomaterials have also been reported to be genotoxic in bivalve mollusks and plants. In addition, nanomaterials derived from chemical synthesis often require highly pure reagents, high temperatures, or complex microfabrication techniques. , The development of novel methods to solve these key issues is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…6 Combining phytoplankton with nanomaterials into biohybrid systems provides the potential to decrease atmospheric CO 2 levels. 7,8 However, the cytotoxicity and high cost of engineered nanomaterials limit the development of sustainable photosynthetic biohybrid systems. For example, most biocompatible materials (e.g., carbon or graphite) exert cyto-and genotoxic effects on stem cells, 9 microorganisms, 10 and even animals.…”
Section: ■ Introductionmentioning
confidence: 99%